Kampanye Budaya Beberes di Media Sosial Instagram - Refi Maulana Yusuf; Dadi Ahmadi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This study discusses the culture of beberes campaign in Kentucky Fried Chicken in introducing self service facilities. The lack of concern for cleanliness is still a big problem in Indonesia, because of the lack of awareness of the importance of cleanliness which is not owned by everyone. Therefore, KFC as a fairly large fast food restaurant began to introduce self service through a campaign called Beberes Culture. The campaign which contains responsibility for the used food containers to be disposed of in its place, wants to restore an independent Indonesian culture and care for the cleanliness of the surrounding environment. There needs to be a campaign media that is capable of carrying out this activity, one of the media chosen by KFC is through Instagram @kfcindonesia. Don't forget to put a hash mark on each upload that says